Production and Characteristics Test of Bio-Char Briquettes from Coconut Shells and Corncobs to Optimize Agricultural Waste in Indonesia - Ramadhana, Adriansyah Karunia; Hidayat, Muhamad Farhan; Muhaji, Muhaji; Abdullah, Muhamad Yunus (Journal of Mechanical Engineering, Science, and Innovation, 2025)
Biomass waste is one of the potentials that can be utilized to become alternative energy that can contribute to sustainable development. With briquetting, waste that previously had no benefit can be used as a renewable energy source. In this study aims to compare the characteristics (moisture content, ash content, volatile matter content, bound carbon content and calorific value) of raw materials (coconut shell, corn cob and tapioca flour) and then test characteristics after the raw materials are briquetted. The results of this study with briquetting of waste were able to produce 3.78% moisture content, 11.7% ash content, 0.869 volatile matter content, 5512 cal/g calorific value and 83.651% bound carbon content. So that briquetting can be one of the innovations to optimize the utilization of waste to be processed into renewable energy.